Reinterpreting Islamic Jurisprudence in the Context of Modern Indonesia: A Comparative Study of Traditional and Contemporary Approaches - Loso Judijanto; Muhammad Aziz; Sabri Sabri (Yayasan Adra Karima Hubbi, 2025)
Background. The dynamic socio-political landscape of modern Indonesia presents a unique challenge and opportunity for the reinterpretation of Islamic jurisprudence (fiqh). Traditional approaches rooted in classical texts often struggle to address contemporary issues such as democracy, human rights, and gender equality.Purpose. This study aims to analyze and compare traditional and contemporary approaches to Islamic jurisprudence within the Indonesian context, focusing on how each responds to modern societal demands.Method. The study involved 288 university students from Chinese, Japanese, and Korean TFL settings, and the data from questionnaires were analysed using appropriate statistical methods.Results. The findings reveal a growing trend among contemporary scholars to contextualize fiqh by embracing maqasid al-shari‘ah (the objectives of Islamic law), while traditionalist views remain significant, especially in rural and pesantren-based communities. The study highlights the coexistence and occasional tension between these approaches, suggesting that a balanced reinterpretation, grounded in both textual integrity and contextual relevance, is essential for Islamic jurisprudence to remain meaningful in modern Indonesia.Conclusion. In conclusion, the research emphasizes the need for an inclusive and dialogic framework that bridges traditional wisdom and contemporary realities.